ANALISIS VEGETASI POHON DI DAERAH TANGKAPAN AIR MATA AIR COKRO DAN UMBUL NILA KABUPATEN KLATEN, SERTA MUDAL DAN WONOSADI KABUPATEN GUNUNGKIDUL - , ALANINDRA SAPUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia has abundant water resources, but the availability of water varies based on spatial and temporal conditions. Climate change, ecosystem destruction in the catchment area, poor water use system, and the increase of water consumption demands result a water crisis. The lack of maintenance, and the change of land cover or ecosystem in spring catchment area decreased water catchment capacity. Therefore it is necessary to conduct a water resource conservation, through an ecological study of tree structure analysis in catchment areas of some springs. The research aims to study the tree structure and composition of vegetation and the role of tree vegetation in hydrological cycle. Vegetation analysis ecologically (tree spesies, diversity index, important value index (IVI), covered, frequency, and density in direct although NDVI analysis), in catchment area: Cokro and Umbul Nila springs in Klaten Regency, Mudal and Wonosadi springs in Gunungkidul Regency. The geology information, soil type, physico-chemic factor, and rainfall are recorded. In addition, modeling the role of vegetation in retaining runoff and infiltration retention are also performed. The research showed that spring catchment area: Cokro, Umbul Nila, Wonosadi and Mudal springs size of 828.4 ha